1996
DOI: 10.1021/ma9604808
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular Micelle Formation of Poly(methyl methacrylate)-graft-polystyrene in Mixed Selective Solvents of Acetonitrile/Acetoacetic Acid Ethyl Ether

Abstract: Unimolecular micelle formation is investigated by means of light scattering for poly(methyl methacrylate)-graft-polystyrene copolymers with low grafted chain densities in dilute solution of mixed selective solvents. Molecular weights of poly(methyl methacrylate) (PMMA) backbone and polystyrene (PS) branch are about 6 × 106 and 9 × 103 g mol-1, respectively, and the grafted chain density ranges from 6 to 17 wt % in terms of PS composition. The mixed solvents are marginally good solvents for PMMA and are nonsolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 34 publications
(61 reference statements)
7
72
1
Order By: Relevance
“…In most cases, interchain association often occurs with intrachain self-folding, which spoils the study and leads to multi-chain micelles coexisting with single-chain micelles [91,92]. To our knowledge, only Kikuchi and Nose [93] experimentally studied intrachain micelle formation. They used polystyrene-g-poly(methyl methacrylate) to observe the formation of thermodynamically stable singlechain multi-flower structures and revealed that the resultant structure was rigid and on average consisted of ca.…”
Section: Hydrophobically Modified Pnipam Copolymer Chainsmentioning
confidence: 99%
“…In most cases, interchain association often occurs with intrachain self-folding, which spoils the study and leads to multi-chain micelles coexisting with single-chain micelles [91,92]. To our knowledge, only Kikuchi and Nose [93] experimentally studied intrachain micelle formation. They used polystyrene-g-poly(methyl methacrylate) to observe the formation of thermodynamically stable singlechain multi-flower structures and revealed that the resultant structure was rigid and on average consisted of ca.…”
Section: Hydrophobically Modified Pnipam Copolymer Chainsmentioning
confidence: 99%
“…For the case of amphiphilic graft copolymers, the existence of intramolecular pearl-necklaces of micelles and cylindrical micelles was argued theoretically and directly observed in simulation studies 28,29 . Also, it was shown experimentally that amphiphilic graft copolymers in dilute solutions form either unimolecular rodlike chains of micelles or unimolecular rodlike micelles, depending on the quality of the solvent 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Intramolecular structure formation of polymers carrying associative groups along the chain backbone have been the subject of experimental (McCormick, 2000;Glass, 2000;Kikuchi and Nose, 1996) and theoretical (Halperin, 1991;Borisov and Halperin, 1997;Koga, 2000, 2001;Koga and Tanaka, 2001) interest in recent years. Knowledge of the intramolecular structure formation of single polymer chains is absolutely essential for an understanding of the molecular mechanism of physical properties of many-chain associating systems, e.g., solution properties of associating polymers and the elasticity of networks whose subchains contain associative groups.…”
Section: Intramolecular Micellization Of Periodic Associating Polymersmentioning
confidence: 99%